2022
DOI: 10.1007/s11242-021-01729-5
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Study of Quasi-Static Loading of Aluminum Closed-Cell Foams Using Weaire–Phelan and Kelvin Tessellations

Abstract: Study of porous materials, in particular closed-cell foams, has always attracted researchers' interest due to the advantages these materials offer in applications where low weight, buoyancy, insulation, or energy absorption is of importance. In this study, quasi-static compressive experimental tests are conducted for low-, medium-, and high-density aluminum foams and their mechanical properties are obtained. In addition, two types of lattice structures based on regular repeating unit cells (Kelvin and Weaire-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…In experimental compression-shear tests of CAF under quasi-static conditions, Xueyan et al [21] observed that an increase in the pore size of CAF increased the yield stress under the same density conditions. Shakibanezhad et al [22] conducted quasi-static compression tests on low-, medium-, and high-density aluminium foams and found that with an increase in foam density, the dense strain decreased, whereas other mechanical properties (such as elastic modulus, yield stress, platform stress, and energy absorption capacity) increased. Li et al [23] studied the mechanical behaviour of CAF under biaxial loading and conducted shear-compression coupling tests by changing the loading angle.…”
Section: Introductionmentioning
confidence: 99%
“…In experimental compression-shear tests of CAF under quasi-static conditions, Xueyan et al [21] observed that an increase in the pore size of CAF increased the yield stress under the same density conditions. Shakibanezhad et al [22] conducted quasi-static compression tests on low-, medium-, and high-density aluminium foams and found that with an increase in foam density, the dense strain decreased, whereas other mechanical properties (such as elastic modulus, yield stress, platform stress, and energy absorption capacity) increased. Li et al [23] studied the mechanical behaviour of CAF under biaxial loading and conducted shear-compression coupling tests by changing the loading angle.…”
Section: Introductionmentioning
confidence: 99%
“…Kelvin and Weaire-Phelan unitcell models were compared to each other in [22]. With the development of the finite element technique, attempts to try and predict properties of metal foams were discussed, based on different modelling techniques [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the mechanical properties and heat transfer in foams indicate negligible differences between the Kelvin cell and Weaire-Phelan cell models. 14,15 Therefore, the present work focuses on Kelvinʼs conjecture. The Kelvin cell is space-filling, and the foam unit cell results from subtracting a sphere from the Kelvin cell.…”
mentioning
confidence: 99%